2021
DOI: 10.1002/tax.12500
|View full text |Cite
|
Sign up to set email alerts
|

One species with a disjunct distribution or two with convergent evolution? Taxonomy of two South American garlics

Abstract: The establishment of species boundaries has been a difficult task for biologists since the beginning of classifications. Within South American Allioideae (= Alliaceae), the delimitation of genera and species has long been a major challenge. Consequently, species‐level nomenclature in these groups has been difficult to elucidate. Ipheion and Tristagma are two closely related South American genera for which the delimitation and circumscription of several species continue to be unclear. Tristagma sessile, a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
7
0
1
Order By: Relevance
“…Even though I. recurvifolium exhibits floral similarities to Tristagma sessile (Phil.) Traub, this is more likely to be a result of convergent evolution of pollination strategies (Sassone et al, 2021). Our results support a unique history for I. tweedieanum and I. recurvifolium and we found no evidence of a hybrid origin or support for a shared genetic background with Tristagma sessile (Figure 2).…”
Section: Mechanisms Of Speciation and Diversification Within Ipheionsupporting
confidence: 61%
See 2 more Smart Citations
“…Even though I. recurvifolium exhibits floral similarities to Tristagma sessile (Phil.) Traub, this is more likely to be a result of convergent evolution of pollination strategies (Sassone et al, 2021). Our results support a unique history for I. tweedieanum and I. recurvifolium and we found no evidence of a hybrid origin or support for a shared genetic background with Tristagma sessile (Figure 2).…”
Section: Mechanisms Of Speciation and Diversification Within Ipheionsupporting
confidence: 61%
“…Moreover, in addition to the habitat differences, the flowers of I. recurvifolium bear a tube and style significantly longer than the other two species (Figure S1a,c; Table S2), suggesting this species is pollinated by different insects, probably Sphingidae (Lepidoptera; Sassone et al, 2021). Shifts in phenology and/or habitat between species would maximize individual fitness by increasing floral visitation, which can explain the lack of interspecific hybrids in nature (Sassone & Giussani, personal observation).…”
Section: Species Variability In Ipheionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural patterns of phenotypic variation are not always congruent with patterns of genetic variation and/or patterns of spatial distribution of species. On the one hand, empirical biogeographic studies have shown that individuals from allopatric populations sometimes appear as phenotypically homogeneous across disjunct geographic ranges, whereas, on the other hand, a careful examination of sympatric individuals sometimes reveals the existence of phenotypically similar but phylogenetically different taxa (i.e., the so-called "cryptic lineages") [1][2][3]. Although different eco-evolutionary scenarios involving recent vicariance, dispersal, or biological introduction, incipient divergence in sympatry, secondary contact, and/or phenotypic convergence may be invoked to explain such overall phenotypic similarity, a question remains: are we sure that these individuals cannot be distinguished based on their phenotypes?…”
Section: Introductionmentioning
confidence: 99%
“…[2,4]. Identifying even a few phenotypic traits involved in the phenotypic differentiation may at the same time inform taxonomy and give insights into the ecological and evolutionary mechanisms leading to the observed geographic and/or genetic differentiation [3,5]. Recent advances in image-based phenotyping offer new opportunities to capture phenotypic complexity [6] and, therefore, to identify new phenotypic traits to distinguish groups of individuals and better understand the eco-evolutionary causes of phenotypic differentiation.…”
Section: Introductionmentioning
confidence: 99%